PCR-Restriction Fragment Length Polymorphism Analysis of Campylobacter jejuni Genes Involved in Lipooligosaccharide Biosynthesis Identifies Putative Molecular Markers for Guillain-Barré Syndrome - Godschalk, Peggy C. R. (American Society for Microbiology, 2007)
Molecular mimicry of Campylobacter jejuni lipooligosaccharides (LOS) by gangliosides in peripheral nerve tissue probably triggers the Guillain-Barré syndrome due to the induction of cross-reactive antibodies. PCR-restriction fragment length polymorphism analysis of C. jejuni genes involved in the biosynthesis of LOS demonstrated that specific genes were associated with the expression of ganglioside mimics and the development of neuropathy.